Knowledge and Practice about COVID-19 among Medical Students - Rafia Hussain, Mehwish Arif, Saadia Ayub, Seema Daud, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Covid-19 pandemic has brought the world to a standstill where the only hope to end this is the prevention and control of the disease. Medical students hold significant importance in this crisis as being the individuals at increased risk as well as future health care providers. Aim: To assess the knowledge and practice regarding Covid-19 Methods: A cross-sectional study was conducted at Lahore Medical and Dental College, Tulspura. The duration of study was three months from Feb 2021 till April 2021 after the approval of synopsis by IRB committee, LMDC. Study Population included final year MBBS students. Sample size was n=113.Sampling technique used was non-probability convenience sampling technique. Data collection was done using a structured questionnaire consisting of three sections viz socio demographic characteristics, knowledge and practice about Covid-19. Data entry and analysis was done using IBM SPSS version 21. Results: Study participants included 48.7% males and 51.3% females. Most of the students 99.1% were aware of the Covid-19 pandemic. About 99.1% students also knew that it is an infectious disease and 96.5% knew that a virus is the causative agent of Covid-19. However, 84.1% had correct knowledge regarding the incubation period of the disease. Maximum respondents 73.5% believed that everyone is equally susceptible to get infected with Covid-19. Fever and cough are the most common symptoms of the disease and internet and electronic media are most common source of information regarding Covid-19. Majority 46% of respondents did not adopt good practice of regular washing of hands. Nearly 63.7% ate healthy food and 73.5% maintained healthy life style focusing on outbreak Conclusion: The medical students had adequate basic knowledge regarding the disease, electronic media and internet being the most common source of knowledge. The practices of mask wearing and adoption of healthy lifestyle were widely adopted yet the practice of hand hygiene and reduced social mobility was poorly conducted.